2022
DOI: 10.1002/jcla.24577
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of hsa_circ_0048122 to predict liver metastasis in early‐stage colorectal cancer

Abstract: Background: Liver metastasis is the primary cause of lethal colorectal cancer (CRC).The predominant risk of poor patient prognosis in early-stage CRC emerges as metachronous liver metastasis. This necessitates the search for potential biomarkers for this metastasis to assess treatment outcomes and provide targeted therapy. Methods:The role of hsa_circ_0048122 in predicting liver metastasis in CRC was probed in this work. This retrospective and multi-center investigation entailed exploration and identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…4 D). Among the 10 ce-circRNA candidates, 0048122 is identified as being involved in colorectal cancer [ 25 ] and 0000644 in bladder cancer [ 58 ]. The other best ce-circRNA candidates ( 0000516, 0087643, 0052523, 0046599, 0042521, 0064288) have not yet been described in the literature as associated with cancer, making them interisting subjects for further experimental validations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 D). Among the 10 ce-circRNA candidates, 0048122 is identified as being involved in colorectal cancer [ 25 ] and 0000644 in bladder cancer [ 58 ]. The other best ce-circRNA candidates ( 0000516, 0087643, 0052523, 0046599, 0042521, 0064288) have not yet been described in the literature as associated with cancer, making them interisting subjects for further experimental validations.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated Cirscan on public multi-level transcript expression dataset from two cancers: colorectal cancer [ 24 ] and hepatocarcinoma cancer [ 25 ] and showed that Cirscan was able to retrieve previously described sponge mechanisms in the top ranked circRNA–miRNA–mRNA subnetworks, as well as identifying novel circRNA sponge candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Cirscan identified a potential novel sponge mechanisms for the hsa circ 0000517, involving the hsa-miR-330-5p that targets genes, for example the oncogene NRAS, enriched in different cancers, such as hepatocellular carcinoma and bladder cancer (Figure 4.D). Among the 10 ce-circRNA candidates, hsa circ 0048122 is identified as being involved in colorectal cancer [25] and hsa circ 0000644 in bladder cancer [53]. The other best ce-circRNA candidates (hsa circ 0000516, hsa circ 0087643, hsa circ 0052523, hsa circ 0046599, hsa circ 0042521, hsa circ 0064288) have not yet been described in the literature as associated with cancer, making them interisting subjects for further experimental validations.…”
Section: Identification Of Known and Novel Sponge Mechanisms In Hepat...mentioning
confidence: 99%
“…In addition, our multiple criteria strategy leads to the calculation of a sponge score for each circRNA-miRNA-mRNA subnetwork, that greatly facilitates the prioritization of experimental validations. We evaluated Cirscan on public multi-level transcript expression dataset from two cancers: colorectal cancer [24] and hepatocarcinoma cancer [25] and showed that Cirscan was able to retrieve previously described sponge mechanisms in the top ranked circRNA-miRNA-mRNA subnetworks, as well as identifying novel circRNA sponge candidates.…”
Section: Introductionmentioning
confidence: 99%